Preserving Indigenous Cultures: Analyzing Geographical Indication Registration for Indigenous People Protection in Indonesia - Alif Muhammad Gultom; Sri Wartini (Journal of Judicial Review, 2023)
Geographical indication (“G.I”) is a designation that indicates the unique and original qualities of a product originating from a particular geographical location. The human factor (Indigenous people) plays a big role in the creation of a geographical indication, in addition to environmental and geographical factors. Preserving the intellectual property rights of Indigenous People through G.I will result in a more advantageous impact on their community, especially for those who rely on G.I products for their livelihood. This not only safeguards their cultural identity and dignity but also enables them to benefit from the commercial value of their intellectual property, whether through direct sales or licensing agreement. Indonesia have ratified the International regulation and issued Law No. 20 of 2016 concerning Trademark and Geographical Indications. The purpose of this research is to evaluate and examine the current status of geographical indication protection in Indonesia and assess if it is being implemented in line with the expectations set forth in the relevant legislation based on the supportive data and previous cases. The paper will then illustrate the impact and advantages for Indigenous communities in preserving and registering their geographical indications, using examples of successful geographical indication registrations from around the world. The type of research method is normative while the approaches employed are statutory and conceptual approaches with an analytical and descriptive research design. Based on the research conducted, the legal framework for protecting G.I has been sufficiently established but the government has not fully prioritized based on the data presented and cases documented. This paper will present several recommendations for the government and other relevant stakeholders.